2008
DOI: 10.1111/j.1442-2018.2007.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Ageism revisited: A study measuring ageism in East Tennessee, USA

Abstract: Research literature over the past 50 years has addressed ageism, but few studies have examined the measurement of ageism or how to combat it. This study utilized Palmore's Ageism Survey to measure the frequency of occurrence of ageism and to examine the types of ageism reported by older adults in the East Tennessee region of the USA. A convenience sample of 247 community-dwelling older adults was recruited from eight senior centers and nutrition sites. The participants ranged in age from 60-92 years. Eighty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 17 publications
2
25
0
1
Order By: Relevance
“…Hard discrimination was also reported more frequently by respondents living in urban areas (large and medium cities) than in rural areas, as confirmed in other research (Johnson and Neumark 1997;McGuire et al 2008). Differences in age composition between urban and rural labour markets have been increased in Poland by the outflow of younger and skilled people from village to cities (Szymańska and Biegańska 2014).…”
Section: Discussion Hard and Soft Discriminationsupporting
confidence: 73%
See 1 more Smart Citation
“…Hard discrimination was also reported more frequently by respondents living in urban areas (large and medium cities) than in rural areas, as confirmed in other research (Johnson and Neumark 1997;McGuire et al 2008). Differences in age composition between urban and rural labour markets have been increased in Poland by the outflow of younger and skilled people from village to cities (Szymańska and Biegańska 2014).…”
Section: Discussion Hard and Soft Discriminationsupporting
confidence: 73%
“…Some studies found higher rates of discrimination in urban areas than in rural areas (Johnson and Neumark 1997;McGuire et al 2008). Urban and rural labour markets can differ significantly regarding the occupational structure and types of companies, culture and social norms of work and work relations, as well as the age composition of workforce.…”
Section: Explaining Age Discrimination: Socio-demographic and Occupatmentioning
confidence: 99%
“…Are Canadians really more ageist than Americans? This study, using Palmore (2001) Ageism Survey, attempts to examine the prevalence of ageism in British Columbia and discuss it's impact on seniors.…”
Section: The Context Of This Workmentioning
confidence: 99%
“…The survey covers only negative forms of ageism and includes examples of stereotypes, attitudes, personal and institutional discrimination. "The respondents were invited to Put a number in the blank that shows how often you have experienced that event: Never = 0; Once = 1; More than once = 2" (Palmore, 2001).…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation